Coupled Thermo-Structural Simulation of Al2618, Al4032, and Al6061 Pistons in a Single-Cylinder Diesel Engine - Baharudin, Agus; Purwanto, Wawan; Setiawan, M. Yasep; Putra, Dwi Sudarno; Arif, Ahmad; Hermanto, Jheri (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
This study presents a thermo-structural finite element analysis of a single-cylinder diesel piston using ANSYS, comparing three aluminum alloys: Al2618-T61, Al4032-T6, and Al6061-T6. A coupled simulation approach was applied, where steady-state thermal results were imported into static structural analysis. Realistic boundary conditions, including applied combustion pressure, symmetry constraints, and cylindrical pin supports, were implemented based on Yanmar TF55 engine geometry. Results indicate that Al6061-T6 experienced the highest deformation and stress, nearing its yield limit at elevated temperatures. In contrast, Al2618-T61 and Al4032-T6 maintained structural integrity, with lower stress and elastic deformation within safe limits. Al4032 demonstrated superior dimensional stability, while Al2618 exhibited better strength under thermal load. These findings validate the importance of coupled thermal-structural analysis and material selection in piston design. The proposed framework offers reliable guidance for developing more durable, thermally resilient pistons for modern diesel engines.